Determinants of Company Value: Evidence from Indonesia's Basic and Chemical Industries: Determinan Nilai Perusahaan: Bukti dari Sektor Industri Dasar dan Kimia Indonesia - Melawati , Hana Oktavia; Nirwana, Nihlatul Qudus Sukma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The global economy is highly interconnected, emphasizing the strategic role of the Basic Industry and Chemicals sector on the Indonesian Stock Exchange (IDX). Specific Background: Firm Value is a crucial indicator for investors, commonly influenced by internal factors such as profitability, firm size, firm growth, and capital structure. Knowledge Gap: Prior research often investigated these financial variables separately or across broad sectors, failing to capture the specific and volatile dynamics of the capital-intensive Basic Industry and Chemicals sector. Aims: This study aims to analyze the simultaneous effect of Profitability, Firm Size, Firm Growth, and Capital Structure on Firm Value within companies listed in this specific sector on the IDX from 2018–2020. Results: Employing a quantitative approach with t-tests, the findings confirm that Profitability, Firm Size, Firm Growth, and Capital Structure all demonstrate a statistically significant relationship with Firm Value. Novelty: By focusing exclusively on this under-researched sector and integrating the four key determinants, this research offers a more contextual and comprehensive analytical approach. Implications: The results underscore the critical need for robust financial and operational strategies, especially concerning optimal capital structure, to maintain high firm valuation and attract continuous investment in the industry. Highlights: Profitability, Firm Size, Firm Growth, and Capital Structure all significantly determine firm valuation. The study focuses exclusively on the unique dynamics of the Basic Industry and Chemicals sector. Improper capital structure management can lead to reduced investor confidence and lower firm value. Keywords: Profitability, Firm Size, Firm Growth, Capital Structure, Firm Value